Construction of an Anthropomorphic Phantom for Use in Evaluating Pediatric Airway Digital Tomosynthesis Protocols - Nima Kasraie; Amie Robinson; Sherwin Chan (Radiology Research and Practice)
Interpretation of radiolucent foreign bodies (FBs) is a common task charged to pediatric radiologists. The use of a motion compensated technique to decrease breathing motion on images would greatly decrease overall exposure to ionizing radiation and increase access to treatment yielding a great impact on clinical care. This study reports on the methodology and materials used to construct an in-house anthropomorphic phantom for investigating image quality in digital tomosynthesis protocols for volumetric imaging of the pediatric airway. Availability and cost of possible substitute materials were considered and simplifying assumptions were made. Two different modular phantoms were assembled in coronal slab layers using materials designed to approximate a one- and three-year-old thorax at diagnostic photon energies for use with digital tomosynthesis protocols such as those offered on GE’s VolumeRAD application. Exposures were made using both phantoms with inserted food particles inside an oscillating airway. The goal of the phantom is to help evaluate (1) whether the currently used protocol is sufficient to image the airway despite breathing motion and (2) whether it is not, to find the optimal protocol by testing various commercially available protocols using this phantom. The affordable construction of the pediatric sized phantom aimed at optimizing GE’s VolumeRAD protocol for airway foreign body imaging is demonstrated in this study which can be used to test VolumeRAD’s ability to image the airways with and without a low-density foreign body within the airways.